THE IMPACT OF GREEN FINANCE INITIATIVES ON ACHIEVING LOW-CARBON ECONOMIES IN THE DEVELOPING WORLD - Gadekar, Sushil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There are increased environmental challenges coupled with the global need to curtail the amount of carbon released into the atmosphere, which prompted the development of green finance as an important tool to support economic development sustainably. The given paper examines the role of green finance programs in the shift towards the low-carbon economies in the developing world. The study is based on empirical data, policy reviews and case studies of the major fast growing economies to understand the role of green bond, climate funds and sustainability linked loans to lower carbon footprint in various elements like energy, transportation and infrastructure. The paper also studies how the regulatory systems, institutional ability and the partnership between the government and the private business can improve the functionality of the green finance. The results indicate that although there is a trend towards the mainstreaming of green finance, its success can be determined by elements like ease of technology, financial literacy, political will as well as investor trust. It is important to note that the paper concludes that the strategic application of green finance can not only facilitate the achievement of climate objectives but also become an opportunity of developing economies to move on an inclusive and resilient development path. Some policy suggestions are provided to enhance green finance systems and make the switch to low-carbon economies in the Global South.